O ensino da geografia em classe hospitalar/domiciliar: desafios, práticas e possibilidades - Silva, Jean Marcos da (2019)
Currently, hundreds of students with temporary or transient special educational needs due to health treatment, begin or continue their educational process in hospital and / or home classes in the state of Goiás. The present work sought to analyze how the teaching-learning process of Geography and related areas in the context of hospital / home class in Goiás, as well as, to understand the main challenges faced by teachers in acting pedagogically in this context and contribute to new teaching possibilities through the use of other languages ​​of teaching. Geography that goes beyond the use of maps, such as music, in order to make the classes more dynamic, creative, interesting and contextualized with the student's reality. The research was conducted with the teachers who work at the Hospital Educational Service Center (NAEH), located within the Special Education Management in the Inclusive Education Perspective, the Inclusion Superintendence, the Goiás State Department of Education (SEDUC). This work emphasized the importance of this specificity of teaching for students in health treatment and / or convalescence and also the importance of teaching geography in a critical, conscious and innovative way, whether in the regular classes or in the classes. Hospitals. In this work, the reports and experiences of teachers, students and family members were recorded under the inference and experience of the researcher in the researched field. This research was based on a qualitative, exploratory and analytical study of the data collected through questionnaires and interviews, using the participant research. Among the evidences we can highlight that the technological resources of audio and video are well used by teachers as a way of mediating content during classes, because it allows the teacher to capture the student's attention with image, sound and movement and with something that this generation of teenagers is well accustomed and uses daily technology in their daily lives; In this sense, we believe that the educational product proposed in this work, the Music Guide (Teaching Through Music In Humanities: A Possible Practice) will enable the teacher to plan and execute his classes in an interdisciplinary way using the contents of the music and the reflections and questions suggested. in the Guide.